Driven to Succeed? Teenagers' Drive, Ambition and Performance on High-Stakes Examinations - John Jerrim; Nikki Shure; Gill Wyness (Institute of Labor Economics (IZA), 2020)
There has been much interest across the social sciences in the link between young people's socioemotional (non-cognitive) skills and their educational achievement. But much of this research has focused upon the role of the Big Five personality traits. This paper contributes new evidence by examining two inter-related non-cognitive factors that are rarely studied in the literature: ambition and drive. We use unique survey-administrative linked data from England, gathered in the lead-up to high-stakes compulsory school exams, which allow us to control for a rich set of background characteristics, prior educational attainment and, unusually, school fixed effects. Our results illustrate substantial gender and immigrant gaps in young people's ambitiousness, while the evidence for socio-economic differences is more mixed. Conversely, we find a strong socioeconomic gradient in drive, but no gender gap. Both academically ambitious and driven teenagers achieve grades around 0.37 standard deviations above their peers, even controlling for prior academic attainment and school attended.
Keywords: I24; J24; 330; socio-economic gaps; gender gaps; aspirations; secondary school; higher education